ASSESSMENT OF DIFFERENTIATION STRATEGY ON THE PERFORMANCE OF THE SUGAR INDUSTRY IN WESTERN KENYA - ONDERE, JUSTUS; SANGORO, MR. OSCAR; AKETCH, MR. ROMAN; OTUYA, DR. WILLIS (IJRDO - Journal of Business Management, 2016)
The uncompetitiveness of the sugar industry in Kenya necessitated this study to be carried out.The purpose of the study was to assess the application of the differentiation strategy on theperformance of the sugar industry in Western Kenya. The study adopted a descriptive surveydesign to collect data and was carried out in western Kenya. It targeted employees of Mumias,Nzoia, West Kenya and Butali sugar companies. Questionnaires, interview schedules andobservation checklists were used as research instruments. Target population was 1851 employeescomprising the management and non management staff making a sample size of 179 employees.Purposive sampling technique was adopted to select employees to participate in the study. Todetermine the validity of the instruments, they were developed and presented to research expertsand my supervisors at the university to establish whether they measured what they intended tomeasure and to modify them accordingly. Test-re-test method was used where the sameinstruments were administered more than once to the same people under identical conditionsthen the performance was compared. For reliability of the results, piloting was carried out atChemelil and Muhoronii sugar firms before the actual field study. Data was analyzed using bothdescriptive and inferential statistics after collection. Mumias Sugar Company was found to beaggressive as compared to the three remaining companies. Thus the company stands to gain interms of corporate image and reputation due to high promotion activities. Lastly, four challengeswere identified facing sugar industry performance in western Kenya. These were governmentpolicy and politics in the management of the firms, liberalization which has led to importation ofcheap sugar from COMESA member countries and Brazil